The "Chauffeur Fracture": Historical Origins of an Often-Forgotten Eponym. (March 2020) - Andreotti, Mattia; Tonon, Francesco; Caruso, Gaetano; Massari, Leo; Riva, Michele A.
This article describes the origin of the term "chauffeur fracture" used to indicate an oblique fracture of the radial styloid process with extension into the wrist joint. This kind of fracture was originally described by the British surgeon Jonathan Hutchinson in 1866. The invention of the automobile increased the incidence of this fracture among chauffeurs and cabdrivers. Indeed, at the beginning of the 20th century, motor vehicles were started by means of a crank-handle connected to the engine, which needed to be turned vigorously clockwise by hand. If the motor started unexpectedly, the crank-handle could jerk back violently and thereby cause a wrist injury due to sudden hyperextension. We retrospectively reviewed the literature and historical articles to better define the historical origins of an often-forgotten eponym. In 1904, the French surgeon Just Lucas-Championnière first evidenced the occupational origin of this fracture, so introducing the term "chauffeur fracture" to identify this injury.